Effect of Additional Magnetograph Observations From Different Lagrangian Points in Sun‐Earth System on Predicted Properties of Quasi‐Steady Solar Wind at 1 AU. Issue 7 (3rd July 2020) - Pevtsov, A. A.; Petrie, G.; MacNeice, P.; Virtanen, I. I.
Abstract: Modeling the space weather conditions for a near‐Earth environment depends on a proper representation of magnetic fields on the Sun. There are discussions in the community with respect to the value of observations taken at several Lagrangian points (L1 –L5 ) in the Sun‐Earth system. Observations from a single (e.g., Earth/L1 ) vantage point are insufficient to characterize rapid changes in magnetic field on the far side of the Sun. Nor can they represent well the magnetic fields near the solar poles. However, if the changes in sunspot activity were moderate, how well would our predictions of the solar wind based on a single viewing point work? How much improvement could we see by adding magnetograph observations from L5, L4, and even L3 ? Here, we present the results of our recent modeling, which shows the level of improvement in forecasting the properties of the solar wind at Earth made possible by using additional observations from different vantage points during a period of moderate evolution of sunspot activity. As an example, we also show the improvements to the solar wind forecast from adding a single observation of the southern polar area from out‐of‐ecliptic spacecraft at −30° heliographic latitude vantage point. Key Points: Role of observations from different Lagrange points for solar wind prediction has been investigated Artificial data and model‐to‐model comparison are used For prediction of solar wind at L1 /Earth, observations from L5 yield larger improvement as compared with L4